Design of a Mathematics Teaching Module for Elementary School Based on Ethnomathematics of Buton Traditional Houses to Improve Numerical Literacy Skills - Ekadayanti, Waode; Ili, La; Kadir; Yanti, Noer Rakhmat; Hesti (FKIP Universitas Halu Oleo, 2024)
This study aims to design an ethnomathematics-based mathematics teaching module for elementary school, focused on the Traditional House of Buton, to improve numerical literacy skills and assess the feasibility and student responses to the module. The research method used is Research and Development (R&D), following these stages: problem identification, design, validation, implementation, and evaluation. The results show the successful design of the module, which is valid with an average construct validation score of 0,775 and content validation score of 0,772, both categorized as